Branding Strategy for Tourism Industry Development Talun District, Cirebon Regency - Sudiana Wachyudi; Tia Listiaty (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Branding is essential for tourist attractions and government agencies, one of which is improving the image and reputation of a tourist attraction or institution so that the wider community can know it. There needs to be an appropriate strategy from the Talun District government, which is the authority in tourism development in Talun District, so the author is interested in examining the branding strategy carried out by Talun District in developing the tourism sector as a tourist destination. This research uses a descriptive type of research with a qualitative approach. The Talun District Government of Cirebon Regency plans the construction of the "Wisata Talun Ngangeni" to improve the welfare of rural communities and stimulate the regional economy. In addition to promotion through digital tourism, the participation of local communities is needed to maintain and develop innovations in the area. However, it is only possible to have a positive impact on branding tourism culture with digital tourism. Several forms of digital tourism promote tourism using inappropriate and deviant nuances. Usually, children and adolescents often receive such adverse effects.